Physical characterization of paracetamol granule preparation using goroho banana starch as binder and disintegrant - Mutmainnah, Mutmainnah; Abdullah, Abulkhair; Lewa, Sandra; Muhlis, S. Masitah (Universitas Mataram, 2025)
The research aims to formulate Goroho banana starch (GBS) as a binding and disintegrating agent in paracetamol (PCT) granule preparations. PCT granules were made using GBS as a binding agent in 3 concentrations of 6, 8, and 10%, respectively. PCT granules using GBS as a disintegrating agent were made with three concentrations of 10, 15, and 20%, respectively. Paracetamol granules are made using the wet granulation method. Granules were evaluated using six parameters: flow rate, angle of repose, water content, bulk density, tapped density, and compressibility index. GBS as a binder showed good physical properties. F1 (6% GBS) showed a flow rate of 8.1 g/sec, an angle of repose of 22.9 degrees, a water content of 1.2%, and a compressibility index of 19.3%. F2 (8% GBS) shows a flow rate of 8.5 g/sec, an angle of repose of 18.5 degrees, a water content of 1.3%, and a compressibility index of 17.6%. F3 (10% GBS) shows a flow rate of 9.0 g/sec, an angle of repose of 21.5 degrees, a water content of 1.4%, and a compressibility index of 19.3%. 8% GBS showed the best physical properties as a binding agent for PCT granules. GBS as a disintegrating agent, shows excellent physical properties. F4 (10% GBS) shows a flow rate of 12.9 g/sec, an angle of repose of 17.0 degrees, a water content of 4.3%, and a compressibility index of 13.3%. F5 (15% GBS) shows a flow rate of 11.4 g/sec, an angle of repose of 18.0 degrees, a water content of 1.4%, and a compressibility index of 14.5%. F6 (20% GBS) shows a flow rate of 10.7 g/sec, an angle of repose of 23.0 degrees, a water content of 3.5%, and a compressibility index of 14.6%. 10% GBS showed the best physical properties as a disintegrants agent for PCT granules.